Implementasi Sistem Kendali Adaptif Pada Rangkaian MPPT Sebagai Catu Daya Node WSN - Risa Farrid Christianti (Journal of Telecommunication, Electronics, and Control Engineering (JTECE), 2019)
The implementation of the wireless sensor network (WSN), which is a part of the Internet of Things (IoT) technology, requires controlled power supply that can operate continuously and adaptively. With the solar cell power generation technology or photovoltaic (PV), it can provide a source of power supply for the WSN system in areas far from conventional electricity system services. But the implementation of conventional solar cells has a low efficiency, because it is strongly influenced by external factors, including the intensity of sunlight. The Maximum Power Point Tracker (MPPT) system is often used to overcome these problems. MPPT is able to optimize the performance of solar cells to produce the best efficiency, by maintaining the solar panel voltage at its optimum voltage (Vs = Vm), as well as maximizing the transfer of power from the solar panel to the battery. Because the power on the converter output is the result of multiplying Vb and Ib, while the battery voltage is assumed to be constant during the control cycle. In this study, the design and implementation of the WSN rationing system with sources of solar cells and MPPT control circuits were carried out. Microcontrol-based devices as a maximum power point regulator (MPP) of solar cells are implemented with adaptive methods. The results obtained are MPPT output voltage fluctuating between 3.28V to 9.27V for input voltage range of 3.4 to 9.67V.